2006
DOI: 10.1111/j.1439-0396.2006.00629.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the tryptophan requirement of lactating sows. Part 1: Estimation of the tryptophan requirement by performance

Abstract: Mature sows were evenly assigned to six dietary treatments, which differed only in the concentration of total (apparent ileal digestible, AID) tryptophan (Trp) amounting per kg feed to 1.2 g (0.8 g) to 4.2 g (3.8 g) in diets 1-6. For a total of 72 lactations (28 days) sows' feed intake was measured daily and body weight was measured on day 110 of pregnancy and on days 1 and 28 of lactation. Litter size was standardized to 10-12 piglets within 1 week after farrowing. The piglets were weighed at days 1, 21 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 27 publications
3
21
2
Order By: Relevance
“…Sows were fed 2.9 kg/d provided in 2 equal meals at 0900 and 1400 h. Then, sows were allotted to 1 of the 2 lactation diets (differing in their Trp content) according to their BW and backfat depth measured at 1 mo after insemination to have similar body conditions in the 2 groups. Lactation diets were formulated to provide 25% more (Trp+) or 25% less (Trp−) of total Trp:Lys than the value that maximizes the ADFI of multiparous sows in Paulicks et al (2006). The Trp+ diet was obtained through addition of 0.12% l-Trp in the Trp− diet.…”
Section: Animals and Housingmentioning
confidence: 99%
See 2 more Smart Citations
“…Sows were fed 2.9 kg/d provided in 2 equal meals at 0900 and 1400 h. Then, sows were allotted to 1 of the 2 lactation diets (differing in their Trp content) according to their BW and backfat depth measured at 1 mo after insemination to have similar body conditions in the 2 groups. Lactation diets were formulated to provide 25% more (Trp+) or 25% less (Trp−) of total Trp:Lys than the value that maximizes the ADFI of multiparous sows in Paulicks et al (2006). The Trp+ diet was obtained through addition of 0.12% l-Trp in the Trp− diet.…”
Section: Animals and Housingmentioning
confidence: 99%
“…However, it is not known whether the degree of insulin resistance could vary within sows having similar body conditions and be related to ADFI. A deficient as well as an excessive dietary supply of Trp impairs the appetite of lactating sows (Lewis and Speer, 1974;Paulicks et al, 2006). The actual recommendation for the Trp:Lys ratio in the lactation diet is 18% (Dourmad et al, 1991;NRC, 1998) but was recently estimated at 24% on the basis of feed intake and uremia (Pampuch et al, 2006;Paulicks et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both diets were provided in pellets and their compositions are presented in Table 1. Tryptophan concentration in the lactation diet was close to the recommendation of Paulicks et al (2006) to prevent any 468 E. Mosnier et al…”
Section: Introductionmentioning
confidence: 63%
“…Among factors controlling the voluntary feed intake of the lactating sow, some nutrients can be suspected to interfere with appetite when inadequately supplied. For example, Paulicks et al (2006) reported that sows fed a lactation diet supplying 2.4 g/kg of tryptophan (Trp) consumed more feed, had attenuated body weight loss and weaned heavier piglets than sows fed a diet containing 1.9 g/kg of Trp, as recommended by the National Research Council (NRC 1998). However, these authors observed a decreased feed intake and an increased body weight loss in lactating sows when the dietary supply of Trp exceeded 2.4 g/kg, probably because of impairment in Trp homeostasis.…”
Section: Introductionmentioning
confidence: 98%